FINAL ACT: THE LAST MOMENTS OF VARGAS'S GOVERNMENT (1954) ACCORDING TO THE NEWSPAPERS O ESTADO DE S. PAULO (OESP) AND ULTIMA HORA (UH) - Fidelis, Thiago [UNESP] (Pontificia Univ Catolica Sao Paulo, 2017)
The main purpose of this article is to analyze how two different newspapers: O Estado de S. Paulo (OESP), from Sao Paulo; and Ultima Hora (UH), from Rio de Janeiro, profiled the last moments of Vargas's government, by promoting a temporal cut, from the assault against the journalist Carlos Lacerda and the Air Force Commander Rubens Vaz, in August, 5th, 1954, to the president's suicide, in August, 24th. This article has a descriptive analysis by the newspapers, and we indicate as conclusion that the newspapers were in opposite camps, seeking to defend their perspectives: OESP with a intense critical against Vargas, pointing it like the biggest problem of the political of the Brazil in that moment, while the UH endeavored to build the president's image in a positive way, putting it as the great name of the brazilian political history, factor still more evidenced after his tragical death.
Keywords: O Estado de S; Paulo; Ultima Hora; Getulio Vargas; Assaulton Rua Tonelero